Course Review Horay (CRH) Learning Model to Improve Mathematical Learning Outcomes of Integers Materials - Hery Setiyawan; Abdillah Abdillah (IAIN Ambon, 2019)
One of the problems in the learning process of class V SD Al-Manar Surabaya in the academic year 2019-2020 integer material is the teacher uses lecture methods that make students quickly bored and passive. The impact is students have difficulty accepting lessons well and learning outcomes are less than KKM. Therefore, to overcome these problems the researchers applied the course review horay (CRH) learning model. CRH can make students more active and not feel bored. In addition, the application of the course review horay learning model can focus students in learning, so students will more easily receive the material well. The purpose of this study is to describe an increase in learning outcomes after applying the course review horay (CRH) learning model of mathematics in integer material in fifth grade students of SD Al-Manar Surabaya. This type of research is a classroom action research that has been carried out in two cycles with an indicator of research success by 75%. The subjects of this study were 28 students in grade V-B SD Al-Manar Surabaya, consisting of 14 male students and 14 female students. The results showed that learning outcomes have increased with the percentage of completeness of the first cycle 64.28% and the second cycle 85.71%. Thus it can be concluded that the course review horay (CRH) learning model can improve mathematics learning outcomes of integer material in fifth grade students of SD Al-Manar Surabaya.